Restoration of non-carious cervical lesions with ceramic inlays: A possible model for clinical testing of adhesive cements - Michal Staninec; Grant H Tsuji (Wolters Kluwer Medknow Publications, 2012)
Introduction: There are many luting cements coming to market which claim to be adhesive, but there is no clinical protocol currently for testing these claims. There is a standardized protocol for testing direct restorations bonded to dentin and it is used extensively. Case Report: We describe a clinical procedure for restoring a non-carious cervical lesion (NCCL) with a ceramic inlay using Computer-Aided Design and Computer-Aided Manufacturing (CAD-CAM) technology and an adhesive resin cement.The procedure was straightforward and the result was good at one month. Discussion: NCCL's can be restored with CAD-CAM technology in one appointment. This technique can be used to clinically test adhesion of luting cements to dentin, similarly to the current standard for direct restorations.